Quantitative analysis of perindopril erbumine in pharmaceutical preparations by spectrophotometry via ternary complex formation with Zn(II) and eosin and charge transfer complexation with iodine. Issue 2 (2011) - Rahman Rahman, Nafisur Nafisur; Rahman Rahman, Habibur Habibur
Abstract : Two simple, sensitive and accurate spectrophotometric methods have been developed for the analysis of perindopril in pharmaceutical preparations. Method A is based on the formation of ternary complex between zinc(II), eosin and the perindopril, which is extractable with chloroform. The absorption spectrum exhibits a band peaking at 510 nm. Method B is based on the interaction of drug with iodine in dichloromethane resulting in the formation of charge transfer complex which absorbs maximally at 365 nm. Beer's law is obeyed in the concentration range 10–200 μg/ml and 10–180 μg/ml with molar absorptivity of 2.25×10 3 and 3.71×10 3 l/mol·cm for methods A and B, respectively. The detection limits for methods A and B are 0.49 and 0.90 μg/ml, respectively. The optimum experimental conditions for the proposed procedures are investigated. Statistical comparison of the results with the reference method shows excellent agreement and indicates no significant difference between the methods compared in terms of accuracy and precision.